Estimation of Air Pollutant Emissions from Heavy Industry Sector in North Korea - Young Won Lee; Yong Pyo Kim; Min Ju Yeo (Aerosol and Air Quality Research)
Abstract This study aims to estimate the amount of air pollutants emitted from heavy industrial facilities in North Korea. The heavy industry sector in North Korea was classified according to the South Korean definition, and the air pollutant emissions that it generated were estimated for 2017. Emissions of carbon monoxide (CO), nitrogen oxides (NOx), and sulfur oxides (SOx) by the heavy industry sector in North Korea were 22, 73, and 31%, respectively, of those in South Korea’ air pollutant emissions. Moreover, the CO, NOx, and SOx emissions comprised 0.6, 124, and 24%, respectively, of the total air pollutant emission in North Korea estimated from the Emissions Database for Global Atmospheric Research version 5.0 (EDGAR v5.0). Geographically, the NOx emissions were concentrated in the western part of North Korea, while CO and SOx were concentrated in North Hamgyong Province.